Penyuluhan Higiene Dan Sanitasi Lingkungan Pada Tempat Pengolahan Sampah Terpadu (Tpst) Kabupaten Nunukan - Nurmiati Beru; Zamli Zamli (-, 2026)
The inadequate implementation of environmental hygiene and sanitation at the Integrated Waste Processing Facility (TPST) increases the risk of occupational health problems and workplace accidents among waste management workers. This community service program aimed to enhance participants’ knowledge, skills, and awareness regarding the application of environmental hygiene and sanitation in accordance with health standards. The program was conducted at the TPST of Nunukan Regency and involved 10 participants. The methods included health education, interactive discussions, demonstrations on the proper use of personal protective equipment (PPE), practical training on hygiene and sanitation practices, mentoring, and skills evaluation. The evaluation results showed that 8 participants (80%) were able to apply environmental hygiene and sanitation principles appropriately, while 2 participants (20%) still required further assistance. In addition to improving participants’ competencies, the program promoted a cleaner, healthier, and safer working environment and strengthened the commitment of TPST management to implementing sustainable hygiene and sanitation practices. Practice-based education combined with mentoring proved to be an effective strategy for strengthening promotive and preventive efforts in the TPST work environment.